Management and Mastery in Implementation of the Individual Education Plan Online in Kuala Lumpur Schools - Norazilla Abdullah; Mohd Hanafi Mohd Yassin (Department of Special Education, 2018)
The use of technology in the evaluation can help make it easier to understand the assessed assessments including online services. This is not the exception of individual education plans in which the Individual Education Plan improves the technology of writing documents to the use of the online Individual Education Plan System (e-RPI) which documents the individual planning and evaluation of the pupils with special needs without leaving the character and elements becoming more organized and systematic. Hence, this study aims to answer the questions of the study on the management and mastery of the Individual Education Plan online. A total of 75 Special Education teachers in Kuala Lumpur participated in this study. This study uses a quantitative approach in the form of field surveys. The instrument used is a set of questionnaire forms adapted from the Individual Education plan management study by Institute on Community Integration (ICI). Meanwhile, the data obtained were analyzed using SPSS 23.0 software and data interpretation using statistical inference method. The findings show that there is no significant difference in the management of the Individual Education Plan online by male and female teachers. There is also no significant difference in teacher experience with the mastery of the e-RPI. Therefore, it is necessary to train teachers to improve their competence and understanding of the work processes and the exposure of the e-RPI concept.